Technostress in medical and allied field: an empirical study among under graduate public health science students of Purbanchal University affiliated colleges in Kathmandu - Thapa, Alina; Thapa, Deependra K.; Sangroula, Raj K.; Thapa, Salina; Shrestha, Arati D.; Balampaki, Pabitra; Karki, Upendra; Chaudhary, Pramodh; Thapa, Janak K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Technostress among students may lead to a higher burden on higher education institutions through a decrease in productivity, dropouts, and deviation from academic work. Students have a different set of characteristics, which makes them an interesting group to be studied. The aim of the study was to find out the status of technostress among respondents. Methods: Analytical study was conducted among 460 undergraduate public health science students of Purbanchal University in Kathmandu valley. The census method was used for data collection. Standard questionnaires and IDI guidelines are used as data collection tools. Data entry was done in Epidata and analysis was done in SPSS. Results: Mean value of 460 respondents was 22.61. Positive correlation was observed between the technostress and stress (p=0.01), depression (p=0.01), and anxiety (p=0.05). Academic productivity has positive correlation with stress (p=0.05) and depression (p=0.05). Stress was significantly associated with grade (p<0.001), depression was significantly associated with grade (p=0.003), techno overload (p=0.004), techno invasion (p=0.023), and anxiety was significantly associated with age (p=0.008), grade (p=0.009), techno overload (p=0.023), techno invasion (p=0.016), techno complexity (p=0.023). Conclusions: The study showed a positive association between technostress and academic qualification. There is a need for an awareness program on technostress and mental health to provide comprehensive knowledge on mental health.